Biomechanical running indicators and neurodynamic functions of an elite athlete with visual impairment in a track and field sprint - Kozina, Z.; Chaika, O.; Safronov, D.; Prokopenko, I.; Kozin, S.; Shkrebtii, Y.; Trubchaninov, M.; Falyova, O.; Shishenko, V.; Ponomarova, N.; Olefirenko, N. (International Journal of Applied Exercise Physiology, 2019)
Introduction: Study of the problem of compensatory development is of great importance for all categories of the population suffering from impaired operation of the visual analyzer. This problem is of particular importance for Paralympians with visual impairment, since in this case the development of compensatory mechanisms serves not only to maintain the quality of life, but also to achieve high athletic performance. Objective: to identify potential compensatory mechanisms of visual impairment in an elite athlete in the Paralympic sprint based on an analysis of the biomechanical characteristics of running and indicators of neurodynamic functions. Methods: A highly qualified athlete participated in the study, specializing in short-distance running and long jump among athletes with visual impairment (category T12). The individual characteristics of the neurodynamic funktions and the results in running for 60, 80,100, 120, 200 m were analyzed and the biomechanical characteristics of the run for 100 m were determined. In total, 36 series of measurements of each indicator were carried out for 5 months. Results:It is shown that the athlete being examined is an atypical sprinter from the point of view of the properties of the nervous system, development and maintenance of speed at a distance, some biomechanical characteristics of running. The subject athlete is a representative of a mobile and strong type of nervous system, which allows her to maintain a higher speed at a distance compared to other athletes for a longer time, which can be considered as a potential reserve. The presence of a small irregularity in the change in the speed and acceleration of the movement of the ankle and knee joints, observed in some steps when lowering the limb after hip removal, was revealed. Conclusion: Revealed a high reliable relationship between the neurodynamic and biomechanical characteristics of the examined female athlete. Improving the biomechanics of running by focusing on the work of a kinestatic analyzer can give an increase in speed at a distance while maintaining it almost to the finish.